Diversidade e sazonalidade de Tabanidae (Diptera) no distrito de Taquaruçu, Palmas, Tocantins - Costa, Mariana Vaz da (Universidade Federal do Tocantins, 2022)
Tabanidae is a family of diptera of the suborder Brachycera, infraorder Tabanomorpha. They are flies popularly known as horseflies, with geographic distribution throughout the globe, except Antarctica. On diversity, have more than 4,434 species formally described, of which 1,205 are for the neotropical region and 488 for Brazil, the state of Tocantins, in turn, has 65 known species. This is the first study aimed at the diversity and seasonality of Tabanids and the abundance of horseflies in equine attractants for the Cerrado of Tocantins. The collections were performed from April 2012 to April 2013, with malaise traps in gallery forest and typical cerrado, analyses were performed in order to compare the composition of the communities and associate the analyses of richness and abundance in the different phytophysiognomies with climatic factors (temperature, humidity and rainfall). Collections carried out in woodland areas with the malaise trap yielded better results in the dry season, with a high abundance of the species Stypommisa aripuana, S. glandicolor, Catachlorops rubiginosus and Esenbeckia osornoi, which were influenced by the high temperatures that occur during the dry months in the biome. In the typical cerrado, high abundance occurred in the rainy season, with high prevalence of the species Fidena lissorhina, Tabanus occidentalis var. dorsovittatus and T. antarcticus, which were influenced by the rainfall rates of the rainy months. Analyses of the rarefaction curves and of the collector, pointed out that the collections were not enough to sample the Tocantins tabanofauna. As for the collections with equine attractants, they were done in eight campaigns, during four months between the dry (June and September) and rainy (November and March) seasons, also in places of typical cerrado. The most prevalent species were S. aripuana and C. rufescens with high abundance in the dry season, F. lissorhina, Tabanus occidentalis var. dorsovittatus and Poeciloderas quadripunctatus in the rainy season. Tabanidae é ...